Why Malaysians join and stay on in a Multi-Level marketing Company - Ong, Cecilia See Kiaw; Ernest Cyril, de Run (The Icfai University Press, 2007)
Studies on the Multi-Level Marketing (MLM) industry have noted its impressive exponential growth in the past 30 years in terms of total volume of sales and number of salespersons involved. The purpose of this study is to identify the reasons why Malaysians join and continue to remain in the industry. It was found that the main reasons for joining and remaining in MLMs can be grouped into financial independence, personal freedom, types of products and benefits, product credibility and incentives. The initial data was collected by interviewing a sample of MLM distributors in Kuching and Kota Samarahan, Sarawak, Malaysia. The findings were then extrapolated onto a questionnaire to a larger sample throughout Malaysia. Generally, the findings indicate that the desire for money and product features made respondents to join and stay on. The management of MLM companies should look more into the development and promotion of the product rather than the method of selling. This paper provides new knowledge of why people remain in MLMs, and this is important to academia as well as for MLM management.